ANALISIS BEBERAPA SENYAWA METABOLIT SEKUNDER PADA TUMBUHAN SUNGKAI (Peronema canescens jack), MALI-MALI (Leea indica), DAN LERAK (Cyathostemma viridiflorum) DARI KHDTK UNIVERSITAS LAMBUNG MANGKURAT - Rahmani Rahmani; Budi Sutiya; Zainal Abidin (Jurnal Sylva Scienteae, 2022)
The potential of plants with medicinal properties is spread in Indonesia, one of which is in the forest area with a special purpose (KHDTK) UNLAM. This study aims to analyze several active compounds, namely the content of flavonoids, saponins, quinones, tannins, steroids, triterpenoids and alkaloids present in Sungkai plants. (Peronema canescens jack), Mali-mali (Leea indica) and Lerak (Cyathostemma viridiflorum). The results of this study were testing the active compounds that were most commonly found in sungkai plants were saponins, tannins and steroids in parts of the root, stem and leave except for steroids only in the stems and leaves. Testing of active compounds in mali-mali and lerak plants. The compounds most commonly found in the roots, stems and leaves were saponins, quinones, tannins and steroids, for flavonoid and triterpenoid compounds were not found in the three plants. The most abundant alkaloid compounds were found in the Mayer reagent in almost all parts of the sungkai, mali-mali and lerak plants except for the leaves, Wagner and Dragendorf reagents also contained compounds but only a few in the sungkai and lerak plant parts.Potensi tanaman yang berkhasiat obat tersebar di Indonesia, salah satunya di kawasan hutan dengan tujuan khusus (KHDTK) UNLAM.Penelitian ini bertujuan untuk menganalisis beberapa senyawa aktif yaitu kandungan flavonoid, saponin, quinon, tanon, steroid, triterpenoid dfan alkaloid yang ada pada tumbuhan Sungkai (Peronema canescens jack), Mali-mali (Leea indica) dan Lerak (Cyathostemma viridiflorum). Hasil dari penelitian ini pengujian ditemukan pada tumbuhan sungkai senyawa saponin, tanin dan steroid pada bagian akar, batang dan daun terkecuali steroid hanya dibagian batang dan daun. Pengujian senyawa aktif pada tanaman mali-mali dan lerak senyawa yang paling banyak ditemukan di bagian akar, batang dan daun adalah senyawa saponin, quinon, tanin dan steroid, untuk senyawa flavonoid dan triterpenoid tidak ditemukan diketiga tumbuhan. Senyawa alkaloid paling banyak ditemukan yaitu pada pereaksi mayer hampir semua bagian tumbuhan sungkai, mali-mali maupun lerak terkecuali dibagian daunnya, pereaksi wagner dan dragendorf juga terdapat senyawa namun hanya beberapa dibagian tumbuhan sungkai dan lerak